Diamond-like carbon films over reconstructive TMJ prosthetic materials: Effects in the cytotoxicity, chemical and mechanical properties - Silva, Alecsandro de Moura [UNESP]; Figueiredo, Viviane Maria Gonçalves de [UNESP]; Prado, Renata Falchete do [UNESP]; Santanta-Melo, Gabriela de Fátima [UNESP]; Ankha, Milagros del Valle El Abras [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP]; da Silva Sobrinho, Argemiro Soares; Borges, Alexandre Luiz Souto [UNESP]; Nogueira Junior, Lafayette [UNESP] (Elsevier, 2019)
Increasingly more young patients have been submitted to reconstruction of the Temporomandibular Joint (TMJ), so, the prostheses must to present more functional longevity. Objective: To evaluate the effect of diamond-like carbon film (DLC)over titanium alloy (Ti6Al4V)and polyethylene (UHWPE)samples, their mechanical and chemical properties and cellular cytotoxicity. Methods: Titanium and UHWPE specimens, with 2.5 cm in diameter and 2 mm thickness were coated through plasma enhanced chemical vapor deposition (PECVD)with DLC or DLC doped with silver (DLC-Ag). Scanning electron microscopy (SEM)morphological analysis, Energy-dispersive spectroscopy (EDS)chemical analysis, scratching test, mechanical fatigue test, surface roughness analysis, and cellular cytotoxicity were performed. Data were statistically analyzed using one-way ANOVA (p < 0.05)or two-way ANOVA and multiple comparison Tukey test. Results: In the SEM analysis, morphological differences were observed on substrates after DLC deposition. The film chemically modified the substrate surfaces, according to the EDS analysis. The initial critical load failure occurred at 6.1 N for DLC and 9.7 N for the DLC-Ag film. The DLC film deposition over the polyethylene promoted a decrease in the polymer's damaged area after mechanical fatigue cycling. The cytotoxicity analysis demonstrated less biocompatibility in experimental groups, when compared to control, however, increased biocompatibility was observed, at 10 days, in all groups. Conclusion: The diamond-like carbon coating enhanced the chemical and mechanical properties from substrates, however modified biological interaction course of the titanium alloy (Ti6Al4V)and polyethylene (UHWPE)samples. Parameters for film deposition remain to be improved in order to obtain best biocompatibility.
Keywords: Diamond like carbon; Plasma enhanced chemical vapor deposition; Polyethylene; Titanium